MSME Marketing Performance during the COVID-19 Pandemic: The Role of Empowered Interaction Capability - Sumaryanto Sumaryanto; Erni Widajanti (Journal of Economics, Business, and Accountancy Ventura, 2022)
The Covid-19 pandemic has had an impact on the marketing performance of MSMEs in Indonesia, as indicated by a decrease in sales. Therefore, various strategies must be carried out to boost the sales, including by implementing marketing innovations and increasing the ability to interact with customers. In addition to examining the effect of marketing innovation, consumer need adaptability, empowered interaction capability, and marketing intelligence on marketing performance, this study also aims to examine the effect of empowered interaction capability on marketing performance mediated by consumer need adaptability and marketing intelligence in Micro, Small and Medium Enterprises (MSMEs) in Banjarsari District during the Covid-19 pandemic. The sample of this study consists of 51 MSMEs spread across Banjarsari District, Surakarta Regency, Central Java. The analytical method used is Partial Least Square Structural Equation Modeling (PLS-SEM). The results of this study show that empowered interaction capability has a significant positive effect on marketing performance. Meanwhile, marketing innovation, consumer need adaptability, and marketing intelligence have no effect on marketing performance. Likewise, consumer need adaptability and marketing intelligence do not mediate the effect of empowered interaction capability on marketing performance. The implication of this research for MSMEs is that MSMEs need to increase empowered interaction capability through increased collaboration and co-creation so that customers are willing to provide ideas or suggestions to the company, thereby increasing company performance.